2021
DOI: 10.1111/jam.15271
|View full text |Cite
|
Sign up to set email alerts
|

Genus Pseudonocardia : What we know about its biological properties, abilities and current application in biotechnology

Abstract: The genus Pseudonocardia belongs to a group of actinomycetes, and is a member of the family Pseudonocardiacea. The members of this genus are aerobic, Gram-positive, non-motile bacteria that are commonly found in soil, plant, and environment. Although this genus has a low clinical significance, however it has an important role in biotechnology due to the production of secondary metabolites, some of which have anti-bacterial, anti-fungal, and anti-tumor effects. The use of phenotypic tests such as gelatinase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 134 publications
0
14
0
Order By: Relevance
“…Differences in microbial signatures between mainland and island also derived from soil properties, especially soil moisture and soil pH (Supplementary Figures S4, S5). For example, bacterial genus Roseiarcus and Kitasatospora were preferred on mainland due to their negative relationships with soil pH (Kämpfer, 2006;Rezaei et al, 2011;Kulichevskaya et al, 2014;Riahi et al, 2022), and fungal genus Mortierella was preferred on mainland due to its close interaction with plant roots (Toju and Sato, 2018). Overall, we found that habitat fragmentation greatly altered the composition of soil bacterial and fungal communities for each island size, and that the soil and plant properties associated with the habitat fragment-induced changes in community composition differed for bacteria and fungi.…”
Section: Discussionmentioning
confidence: 75%
“…Differences in microbial signatures between mainland and island also derived from soil properties, especially soil moisture and soil pH (Supplementary Figures S4, S5). For example, bacterial genus Roseiarcus and Kitasatospora were preferred on mainland due to their negative relationships with soil pH (Kämpfer, 2006;Rezaei et al, 2011;Kulichevskaya et al, 2014;Riahi et al, 2022), and fungal genus Mortierella was preferred on mainland due to its close interaction with plant roots (Toju and Sato, 2018). Overall, we found that habitat fragmentation greatly altered the composition of soil bacterial and fungal communities for each island size, and that the soil and plant properties associated with the habitat fragment-induced changes in community composition differed for bacteria and fungi.…”
Section: Discussionmentioning
confidence: 75%
“…Many Pseudonocardia -specific gene clusters are now available, and their functions, concerning, for example, synthesis of many natural bioactive products ( Miyamoto et al, 2014 ; Caffrey et al, 2016 ; Won et al, 2017 ; Geddis et al, 2018 ; Fang et al, 2019 ; Strecker et al, 2019 ; Subramani and Sipkema, 2019 ), biodegradation of large amounts of industrially discharged environmental pollutants ( Grostern et al, 2012 ; Sales et al, 2013 ; Inoue et al, 2016 ; Yamamoto et al, 2018 ; Qi et al, 2019 ), defense against invading genetic elements ( Doron et al, 2018 ), have been and will continue to be deduced or demonstrated, showing great application potentials in human medicine, animal health, and crop protection, etc. Indeed, current applications of Pseudonocardia have been summarized very recently ( Riahi et al, 2021 ). These beneficial potentials have attracted a great deal of interest in the Pseudonocardia genus.…”
Section: Introductionmentioning
confidence: 99%
“…It is of particular interest that the genus Pseudonocardia has been reported to evolve a mutualistic role with fungus-growing ants to protect the ants from disease by producing bioactive compounds, such as dentigerumycin, pseudonocardones, gerumycins, selvamicin, and attinimicin . However, in recent years, relatively less new natural products were reported from the genus Pseudonocardia derived from the marine environment, with only 19 examples between 2007 and 2021. ,, …”
mentioning
confidence: 99%
“…1 For example, numerous bioactive macrolides have been reported from rare actinomycetes. 2 The genus Pseudonocardia, first reported by Henssen, 3 is a group of rare actinomycetes that can produce secondary metabolites featuring different physicochemical and biological properties, 4 such as the diazaanthraquinone derivatives pseudonocardians exhibiting potent cytotoxicities and antibacterial activities, 5 the macrolides branimycins showing antibacterial activities against both Gram-positive and Gram-negative bacteria, 6 and the polyene antibiotic NPP with potent antifungal activity against Candida albicans. 7 It is of particular interest that the genus Pseudonocardia has been reported to evolve a mutualistic role with fungus-growing ants to protect the ants from disease by producing bioactive compounds, 8 such as dentigerumycin, 9 pseudonocardones, 10 gerumycins, 11 selvamicin, 12 and attinimicin.…”
mentioning
confidence: 99%
See 1 more Smart Citation